Multitasking, but for what benefit? The dilemma facing Nigerian university students regarding part-time working. Issue 8 (16th November 2016) - Gbadamosi, Gbolahan; Evans, Carl; Obalola, Musa Adebayo
Abstract : Students working part-time while studying for a full-time university degree are commonplace in many Western countries. This paper, however, examines the historically uncommon part-time working activities and career aspirations among Nigerian university students. In particular, how working is perceived to contribute to developing employability skills, and whether it is influenced by their self-efficacy. Survey data from 324 questionnaires were collected from a federal university, although the data analysis used a mixed method. The findings indicate that despite low levels of part-time working generally among students, older, more experienced, higher level and female students place a premium on the skills that part-time work can develop. Moreover, self-efficacy and being female is a significant predictor in understanding part-time work and career aspirations. This study offers originality by focusing on students' part-time work, the value working provides and its link with career aspirations, within a relatively unexplored context of Nigeria.